PELATIHAN PENGELOLAAN DAN PEMASARAN PRODUK UMKM SEBAGAI PENDUKUNG USAHA KAWASAN PARIWISATA DI DESA DUWET, KECAMATAN TUMPANG, KABUPATEN MALANG - Pritantina Yuni Lestari; Prima Beauty Kartikasari; Hilda Cahyani; Isnaini Nur Safitri; Aulia Nourma Putri; Siti Rohani (Jurnal Pengabdian kepada Masyarakat, 2024)
This community service is aimed at accommodating the needs of tourism area business actors in Duwet Village in improving the management and marketing of MSME products through Focused Group Discussion (FGD). Participants in this activity are business actors in the tourism area in Duwet village, Malang. This activity is expected to improve the quality of MSME products in Duwet Village through product management and marketing, which then can be implemented to provide better services to visitors to the Duwet Village tourism area. This activity was carried out in some stages, namely planning (to find out the number of participants who were involved and the materials needed for the training), coordination with the related parties (representative of partner village members, travel agent, and tour guide) to ensure the plans made are in accordance with needs, preparation of Focused Group Discussion (FGD) materials, survey to the exact location in the partner village to ensure the prepared materials are suitable with the condition of the village, doing FGD with the, and evaluation which is giving questionnaires to the participants regarding the implementation and materials.